Os livros de ciências: saúde e doenças prevalentes da população negra em uma possível articulação com a Lei 10.639/2003 - Lima , Débora Michele Sales de (2017)
The learning process of the human being can happen according to the experiences they go through, acquired knowledge or a fact they see. For that, learning that elevates this being is necessary, which allows, beyond information, critical thinking. That is why this research attempts, in a succinct yet meaningful way, to discuss this process analyzing the learning material most common in schools; the book. This paper’s main goal is to evaluate 8th grade science textbooks in the way diseases prevalent in African-descendants are presented, considering the possible articulations with Law 10.639/2003 in three textbook collections of Natural Sciences in Junior High School approved by PNLD 2013/2014 for the three-year-period between 2014 and 2016. To achieve this, the concepts of interdisciplinarity and complexity were used, along with a methodological approach through the Grounded Theory, which consists in a qualitative research approach with the goal of discovering considerations and hypothesis based on the collected data, instead of using predetermined data, along with the qualitative base by Minayo. We used the theoretical basis of Morin; Fazenda; concerning interdisciplinarity and the concept of complexity proposed by Morin; Navas and Manechine This way, the categories analyzed were: open codification, axial codification, selective/theoretical codification, Sickle cell anemia, STD/AIDS and Syphilis. For theoretical support, we used the authors: Mukherjee, Andrade, Cunha, Rocha, Oliveira, Debret, Figueiredo, and Mengarda, Mungana, Rocha; Silva, who discuss African-descendants health in general and their health history; and Lajolo, who discusses textbooks, among others who contributed to a better understanding in our research. We received results which proved the need for 8th grade science textbooks to contain diseases prevalent in African-descendants or even signal the diseases in the book are prevalent in this population in order to list the learning difficulties that people with these diseases face in the classroom, daily and in society. The diseases are still treated in textbooks with normalized speech, meaning it discusses sex in a negative aspect and not at all elucidating. In all three collections, we stated the lack of these contents while a racial factor. Our intention is to work the interdisciplinarity that exists between history and science, realizing the importance of that to understand the context and the current conjuncture of the practice of science teaching. What we seek is not the evidence of something bad related to African-descendants; but the equality of right to information, demystifying the leveled prejudice that exists in society. One of the ways of doing that is applying the aforementioned law in a interdisciplinary way, reaffirming the complexity that exists in health subjects approached in Science and trying to reach other levels of teaching. This intersectional view between Biology, Law 10.639/2003 and the contents of science textbooks is of great importance, given that, according to the law, it is mandatory teaching taking into consideration African-descendants, however seeing the subjects present in textbooks, we realized that they are not presented in a way to fulfills the Law. From this it is possible to create alternatives for the application of the same.